How trauma related to sex trafficking challenges parenting: Insights from Mexican and Central American survivors in the US. - Marti Marti Castaner (Public Library of Science (PLoS), 2021)
Sex trafficking, a form of human trafficking for the purpose of commercial sexual exploitation, with a global prevalence of 4.5 million, has pervasive effects in the mental and physical health of survivors. However, little is known about the experiences and needs of Latinx migrants (the majority of sex trafficking victims in the US) after trafficking, particularly regarding parenting. This QUAL-quant study examines how 14 survivors of sex trafficking (mean age = 30) from Mexico and Central America encounter and respond to parenting experiences after escaping sexual exploitation. Combining a bio-ecological model of parenting with Zimmerman's framework on human trafficking we identified how trauma related to sex trafficking can challenge parenting and how relational and contextual pre and post trafficking factors (dis)enable women to respond to such challenges. Psychological consequences of daily victimization primarily manifested in three ways: overprotective parenting in a world perceived to be unsafe, emotional withdraw when struggling with stress and mental health symptoms, and challenges building confidence as mothers. These experiences were accentuated by pre-trafficking experiences of neglect and abuse, forced separation from their older children, poverty post-trafficking, and migration-related stressors. Yet, finding meaning in the birth of their child, having social support, and faith, also enable mothers to cope with such challenges. We conclude that motherhood after surviving sex trafficking presents new challenges and opportunities in the path to recovery from trauma. Interventions at the policy, community and individual level are needed to support survivors of sex trafficking as they enter motherhood.